Genetic analysis of Lamin A/C gene variants in cases of sudden cardiac death admitted to a medico-legal laboratory - Van Niekerk, Chantal (University of Pretoria, 2023)
Dissertation (MSc (Chemical Pathology))--University of Pretoria, 2022.